Mental, neurological and substance use disorders among the Latino migrant population in the United States who visited the Health Windows and Mobile Health Units in 2021 - López Jaramillo, Ana María; Rangel Gómez, María Gudelia; Morales Chainé, Silvia; López Montoya, Alejandra; Lira Chávez, Isaura Angélica; Cruz-Piñeiro, Rodolfo (Frontiers in Public Health, 2023)
Background Mental health is defined by the World Health Organization as a state of wellbeing in which people are aware of their own abilities to cope with the normal stresses of life, work productively and fruitfully, and contribute to their community. Among the minority groups that may be vulnerable to experiencing greater risks for their physical and mental health and full development is the migrant population. The mobile population's migration experience, from their place of origin to destination translates into psychosocial problems and clearly stressful conditions which could be resolved using certain coping strategies. Accordingly, numerous epidemiological studies have found differences in the prevalence of mental health problems between migrants and native-born residents of destination countries, as well as between migrants and their non-migrant co-nationals. Purpose To describe sociodemographic characteristics of the Latino migrant population in the United States who visited the Health Windows (HW) and Mobile Health Units (MHU) in 2021, who may have been at risk for mental, neurological or substance use disorders and agreed to a screening for signs and symptoms of mental health conditions. Method Users of the HW and MHU were offered preventive health services and completed a mental health screening. These variables were registered in SICRESAL. If their results showed signs and symptoms of mental health conditions, they were screened by credentialed professionals from the Psychology Faculty of the National Autonomous University of Mexico. Screened individuals received a diagnosis and specialized care remotely and/or online with the MHU and HW network partners. To analyze sociodemographic variables corresponding to neurological or substance induced mental illness among the Latino migrant population in the United States who visited the Ventanillas de Salud (VDS)/Health Windows (HW), and Unidades Móviles de Salud (UMS)/Mobile Health Units (MHU), during 2021; contingency tables were created showing percentages and chi square with a significant p < 0.05. Findings During 2021 HW and MHU completed a total of 794 mental health screenings of which 84% were completed at HW. Further, 59% were women with an average age of 43, ranging from 7 to 86 years of age. Twenty percent 20% of the population who voluntarily agreed to screening yielded a positive result for some type of mental health symptom or problem. This percentage (37%) was greater among those who consulted MHU. With respect to age, results showed that youth were at greatest risk for mental health problems. Among the screened population, the independent variables, type of Health Window attended, gender, age group, and place of origin are related to the existence of some type of mental health symptom or problem yielding a significance level of <0.05 for depression and anxiety symptoms. Discussion and prospects In this study, as in others, the migrant population that visited the HW and UMS in 2021 reported a greater risk of mental health problems, with symptoms related to depression and anxiety among the socio-demographic variables of gender, age group, and place of origin. Thus, these symptoms relate to being a female aged between 18 and 38 and originating from Mexico. Finally, the possibility of screening the migrant population for signs and symptoms of mental health conditions that attended the Health Windows or Mobile Health Units during 2021, made it possible to refer them to psychology or psychiatry services and improve the quality of life of those who accessed the services and, consequently, that of their families and communities. Limitations The main limitation is associated with the information source since we worked with secondary data and relied on the information provided by those who attended both the HW and the MHU.